(untitled) (Economics and region, 2018)
The purpose of the article is to formulate proposals on the reduction of international approaches to land valuations in the financial statements. International standards regulate the use of different models of land valuation depending on the inclusion of land in the articles of the Statement of Financial Position: «Property, Plant and Equipment» (cost model or revaluation model); «Investment property» (cost model or fair value model); «Non-current assets held for sale» (cost model, revaluation model, fair value model or fair value less selling costs); «Inventories» (cost of inventories or net realizable value). Taking into account the special status of the land as a type of non-current assets that are not depreciated, it is proposed to allocate in the section «Non-current Assets» of the Statement of Financial Position an article «Land parcels» with an estimate of all land parcels at fair value. In other words, to introduce a grouping of long-term tangible assets not in the form of the articles «Property, plant and equipment» and «Investment property», and with the distinction of types of resources (assets) and the requirement of disclosure in the notes of the value of the land occupied by the owner, and leases. A significant advantage of a fair value model compared to a revaluation model is a significantly simplified approach to settlements, since it only involves adjusting the fair value to the amount of gain or loss without the need for a labor-intensive determination of impairment loss through interim payments: recoverable amount, fair value less costs to sell, value in use. For such implementations, the amount of accounting calculations will be substantially reduced, and the reliability of information on land parcels for users of general-purpose financial reporting is significantly increased.